Predicting dredging-associated effects to coral reefs in Apra Harbor, Guam – Part 2: Potential coral effects. (1st March 2016) - Nelson, Deborah Shafer; McManus, John; Richmond, Robert H.; King, David B.; Gailani, Joe Z.; Lackey, Tahirih C.; Bryant, Duncan
Abstract: Coral reefs are in decline worldwide due to anthropogenic stressors including reductions in water and substratum quality. Dredging results in the mobilization of sediments, which can stress and kill corals via increasing turbidity, tissue damage and burial. The Particle Tracking Model (PTM) was applied to predict the potential impacts of dredging-associated sediment exposure on the coral reef ecosystems of Apra Harbor, Guam. The data were interpreted using maps of bathymetry and coral abundance and distribution in conjunction with impact parameters of suspended sediment concentration (turbidity) and sedimentation using defined coral response thresholds. The results are presented using a "stoplight" model of negligible or limited impacts to coral reefs (green), moderate stress from which some corals would be expected to recover while others would not (yellow) and severe stress resulting in mortality (red). The red conditions for sediment deposition rate and suspended sediment concentration (SSC) were defined as values exceeding 25 mg cm −2  d −1 over any 30 day window and >20 mg/l for any 18 days in any 90 day period over a column of water greater than 2 m, respectively. The yellow conditions were defined as values >10 mg cm −2  d −1 and <25 mg cm −2  d −1 over any 30 day period, and as 20% of 3 months' concentration exceeding 10 mg/l for the deposition and SSC, respectively. The model also incorporates the potential for cumulative effects on the assumption that even sub-lethal stress levels can ultimately lead to mortality in a multi-stressor system. This modeling approach can be applied by resource managers and regulatory agencies to support management decisions related to planning, site selection, damage reduction, and compensatory mitigation. Highlights: This is the first application of PTM to predict coral response to dredging effects. Stoplight indicators were developed to represent coral responses to dredging. The model predicts the spatial area and location of potentially affected habitat. Data could be used in alternatives analysis to select sites with the least impact. Data could be used to design and implement mitigation for predicted coral impacts.